Concentration and distribution of sialic acid in human milk and its correlation with dietary intake - Xie, Qiaoling; Xu, Yuhan; Zhang, Wei; Zhu, Meizhen; Wang, Xinyue; Huang, Jiale; Zhuang, Yingying; Lan, Hui; Chen, Xiaoxuan; Guo, Dongbei; Li, Hongwei (Frontiers in Nutrition, 2022)
Purpose This study evaluates the content, distribution, and changing trend of sialic acid in human milk and the correlation between dietary intake of sialic acid and that in human milk. Methods The study included 33 mothers of full-term and exclusively breastfed infants. At least 2 ml of milk was collected on the 3rd, 8th, 30th, and 90th day after delivery, and 24-h diet recalls of the lactating mothers were obtained each time. The correlation of human milk sialic acid concentration with lactating women's dietary sialic acid intake during lactation was analyzed by statistical analysis software SPSS. Results The average concentration of sialic acid in colostrum, transition, and 1 and 3 months were 1,670.74 ± 94.53, 1,272.19 ± 128.74, 541.64 ± 55.2, and 297.65 ± 20.78 mg/L, respectively. The total sialic acid concentration in colostrum was about 5.6 times higher than that at 3 months (P < 0.001). The average dietary sialic acid intake of lactating mothers on the 2nd, 7th, 30th, and 90th day after delivery were 106.06 ± 7.51, 127.64 ± 8.61, 120.34 ± 10.21, and 95.40 ± 6.34 mg/day, respectively. The intake of sialic acid was relatively high on the 7th day, and there was no significant difference in dietary intake of sialic acid on different days (P < 0.05). In addition, there was no correlation between the intake of dietary sialic acid and the content of total sialic acid and various forms of sialic acid in milk (P < 0.05). Conclusion During the lactation period, the distribution of sialic acid in breast milk is relatively stable and its content fluctuates greatly, which may not be affected by the mother's diet, but mainly depends on the self-regulation oft physiological needs.